Sistem penilaian kenaikan pangkat pensyarah secara sistemetik berasaskan sistem bantuan keputusan berkumpulan - Ismail, Siti Nurbaya (2006)
Manual process of the lecturer’s promotion assessment is commonly involved complicated process. There are a lot of arguments occurred during this process as more than one examiner involve. As the consequences, the assessment objective to evaluate lecturers’ performances might not be achieved and may also result in ineffective and inefficient process. The purpose of this project is to develop a system prototype for assessing the applicants’ qualifications during promotion assessment process. In this project, Decision Support System (DSS) techniques are proposed to improve the current process with the combination of Groups DSS (GDSS), Webbased DSS, and Model-based DSS along with Delphi facilitator. Linear Summations Technique has been used for the modeled and applied in assessment calculation to calculate the score. The evolution prototype approach and UML modeling technique have been applied as the development methodologies to build the new system. This project shows that the new system can supports the assessment process and help the admin to manage it.